Psychosocial community work after disaster - Ajduković, Dean (2004)
Unlike the individual traumatisation, disasters, wars and massive terrorist attacks are cases in which hundreds and thousands of people are exposed to trauma in a short period of time leading to multiple consequences that extend beyond the affected individuals and the incapaciting symptoms of trauma. Social milieu in which the survivor of individual trauma and survivors of mass traumatisation are embedded is qualitatively different, having important consequences for recovery. From a psychological perspective, the special case is organized violence since it is intentional, designed to hurt and destroy people, trauma is inflicted at selected groups and individuals in order to send a symbolic message to other people and communities and violence has a clear instrumental and political purpose. The search for meaning of what has happened is extremely difficult, but people use different coping strategies ranging from spiritual to scape-goating. At the same time people feel that gross injustice has been done to many of them and that their basic rights as human beings have been violated. The task of effective community-based interventions is to help facilitate psychosocial reconstruction of communities, decrease social tensions among groups with conflicting interests, provide treatment for the traumatized individuals and work towards re-connecting community